Proceso de atención de enfermería en adulto joven con neumonia bacteriana - Junco Tapia, Hugo Alberto (2018)
The clinical case presented deals with a female patient with a history of Cerebral Palsy in Children, which was taken to the emergency room of the General Hospital Martin Icaza, after assessing the symptoms presented and analysis of the examinations performed, the medical diagnosis was defined : Bacterial pneumonia; As the causative agent of the pathology we have Streptococcus pneumoniae. The nursing professionals carried out the Nursing Care Process, through which they could provide timely care to the patient, and thus contributed to the quick recovery of the state of health.